Analisis Daya Saing Ekspor Rumput Laut Indonesia: Perbandingan dengan Korea Selatan dan Tiongkok Periode 2015-2024 - Poppy Litasari; Erlyna Wida Riptanti; Indah Nurhidayati (Universitas Galuh, 2026)
Seaweed is one of the marine commodities that has high economic and ecological value and plays an important role in global industry. Indonesia leads in the export volume of raw seaweed (HS 121221) in the global market, but with an export value lower than that of South Korea and China. This study aims to compare the market share and export competitiveness of Indonesian raw seaweed with South Korea and China using the International Market Share Index (IMS), Trade Competitiveness Index (TCI), Revealed Comparative Advantage (RCA), and Revealed Symmetric Comparative Advantage (RSCA) over the period of 2015-2024. The results indicate that Indonesia's market share is smaller than that of South Korea but higher than that of China during the study period, averaging 29.30% of total global exports. In terms of competitiveness, Indonesia demonstrates stronger competitiveness than South Korea and China, with average calculations over the study period showing a TCI of 0.93, an RCA of 29.32, and an RSCA of 0.93. These results indicate Indonesia's potential to increase the export value of raw seaweed.